IVR systems used in call center management: a scientometric analysis of the literature - Coman, Ecaterina (Frontiers in Computer Science, 2025)
IntroductionIn an era where technology is revolutionizing the way business is done, specialists are continuously developing Interactive Voice Response (IVR) systems used in call centers in an attempt to meet the ever-changing needs of both customers and businesses. Before investing in an IVR system, call center managers must have a clear picture of the advantages and challenges associated with this technology, and for researchers, it is important to know what are the emerging topics that could be future research directions in the field. However, there is a lack of comprehensive reviews that present an overview of how IVR systems are used in call centers, and this paper aims to fill this gap in the literature by conducting a scientometric research on scientific production in the field.MethodsA total of 284 documents indexed in the Web of Science database between 1991 and 2023 were analyzed using VOSviewer software. The scientometric analysis included a semantic examination of research trends and thematic clustering within the field.ResultsThe semantic analysis of scientific production highlighted four main research directions: Automatic Speech Recognition, IVR flow optimization, Reliability of IVR systems as a methodology for studies, and Human-Computer Interaction for Development (HCI4D). These clusters highlight the intellectual structure of the field.DiscussionThe paper discusses the general intellectual structure of the field, with the four semantic groups being reviewed. Additionaly, emerging topics were identified and the advantages and challenges that accompany the use of this technology in call centers were discussed.